Notched strength of carbon fibre/epoxy composite laminates with a circular hole; [Kerbfestigkeit von Kohlefaser/Epoxid-Verbund-Laminaton mit runden Öffnungen] - Govindan Potti P.K.; Nageswara Rao B.; Srivastava V.K. (My University, 2025)
This paper improves the two stress fracture criteria proposed by Whitney and Nuismer (known as the point stress criterion and the average stress criterion) to predict the strength of composite laminates with a circular hole. In the point stress criterion, it is assumed that the failure occurs when the stress over some distance (d0) away from the notch is equal to or greater than the un-notched laminate strength. In the average stress criterion it is assumed that failure occurs when the average stress over some distance (a0) ahead of the notch equals the unnotched laminate strength. Both stress fracture criteria are two parameter models based on the unnotched strength (σ0) and a characteristic dimension (d0 ora0). A simple relation is used for the characteristic length to improve the accuracy while evaluating the notched strength of carbon/epoxy composite laminates. The analytical results are compared well with the existing test results of AS4-carbon/948 Al epoxy [0/90]4s and [0/ ± 45/90]2S composite laminates with various hole diameters and specimen widths. © 1999, Springer-Verlag.